How Can the Financing Constraints of SMEs Be Eased in China?-Effect Analysis, Heterogeneity Test and Mechanism Identification Based on Digital Inclusive Finance - Jianwei Li; Renyi Wei; Yuanyuan Guo (Frontiers in Environmental Science, 2022)
Due to the impact of COVID-19 and other factors, SMEs are increasingly facing the contradiction of financing constraints. In order to explore feasible ways to ease the financing constraints of SMEs, we further incorporate digital inclusive finance into the analytical framework of financing constraints of SMEs, and test the causal relationship between them by using models such as two-way fixed effects model and moderated intermediary effect model. We find that digital inclusive finance can effectively alleviate financing constraints of SMEs, and this phenomenon is particularly significant in private enterprises and family enterprises. In addition, the mitigation effect of digital financial inclusion is more like icing on the cake, and it cannot provide practical assistance to small and medium-sized enterprises with poor business conditions. Further research also finds that commercial credit seems to be an effective channel for digital financial inclusion to alleviate financing constraints of SMEs, but corporate leverage also plays an important role in this process, playing a negative moderating role. In general, our study strengthens the effectiveness of digital inclusive finance in alleviating financing constraints of SMEs, at the same time, confirming the existence of commercial credit channels and the moderating effect of enterprises’ lever ratio and providing a feasible direction for alleviating financing constraints of enterprises.